The Keynesian Equations and the Balance of Payments - Bronfenbrenner, M. (Review of Economic Studies, 1940)
The Keynesian Equations and the Balance of Payments Get access M. Bronfenbrenner M. Bronfenbrenner Chicago, Illinois Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 7, Issue 3, June 1940, Pages 180–184, https://doi.org/10.2307/2967405 Published: 01 June 1940